In the following question I have to present the bilinear form as sum of squares with Lagrange method.


However I don't know how I can do it here since none of the coefficients here is squared. I have seen the following solution, however I don't know how to reach it:


I don't understand the logic here.

What are the formulas that were used to "complete the square" here?




Difference of two squares: $$ a^2-b^2=(a+b)(a-b). $$ Now put $a=x+y$ and $b= x-y$. Then $a+b=2x$, $a-b=2y$, and $$ (x+y)^2-(x-y)^2 = 4xy $$

  • $\begingroup$ Thank you! It's quite clear. $\endgroup$ – Alan Oct 3 '15 at 12:05

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.